Systematic review of use of β-blockers in sepsis - Cyril Jacob Chacko; Shameer Gopal (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: We proposed a review of present literature and systematic analysis of present literature to summarize the evidence on the use of β-blockers on the outcome of a patient with severe sepsis and septic shock. Material and Methods: Medline, EMBASE, Cochrane Library were searched from 1946 to December 2013. The bibliography of all relevant articles was hand searched. Full-text search of the grey literature was done through the medical institution database. The database search identified a total of 1241 possible studies. The citation list was hand searched by both the authors. A total of 9 studies were identified. Results: Most studies found a benefit from β-blocker administration in sepsis. This included improved heart rate (HR) control, decreased mortality and improvement in acid-base parameters. Chronic β-blocker usage in sepsis was also associated with improved mortality. The administration of β-blockers during sepsis was associated with better control of HR. The methodological quality of all the included studies, however, was poor. Conclusion: There is insufficient evidence to justify the routine use of β-blockers in sepsis. A large adequately powered multi-centered randomized controlled clinical trial is required to address the question on the efficacy of β-blocker usage in sepsis. This trial should also consider a number of important questions including the choice of β-blocker used, optimal dosing, timing of intervention, duration of intervention and discontinuation of the drug. Until such time based on the available evidence, there is no place for the use of β-blockers in sepsis in current clinical practice.